2019
DOI: 10.3390/nu11102523
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Glutathione and Cystathionine β-Synthase in Ovarian Cancer Treatment by Selenium–Chrysin Polyurea Dendrimer Nanoformulation

Abstract: Ovarian cancer is the main cause of death from gynecological cancer, with its poor prognosis mainly related to late diagnosis and chemoresistance (acquired or intrinsic) to conventional alkylating and reactive oxygen species (ROS)-generating drugs. We and others reported that the availability of cysteine and glutathione (GSH) impacts the mechanisms of resistance to carboplatin in ovarian cancer. Different players in cysteine metabolism can be crucial in chemoresistance, such as the cystine/glutamate antiporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 82 publications
(134 reference statements)
1
45
0
Order By: Relevance
“…As a carbon source, glutamine supplies the tricarboxylic acid (TCA) cycle with oxaloacetate, α-ketoglutarate, and acetyl-CoA, thus being responsible for ATP and macromolecules synthesis, preferentially replacing glucose in certain tumors [ 15 , 16 , 17 ]. Furthermore, glutamine is a precursor of glutamate, which is necessary for the synthesis of non-essential amino acids and glutathione (GSH), the most important reactive oxygen species (ROS) scavenger and detoxifying agent [ 18 , 19 ].…”
Section: Glutamine and Glutamate Metabolism In The Central Nervousmentioning
confidence: 99%
“…As a carbon source, glutamine supplies the tricarboxylic acid (TCA) cycle with oxaloacetate, α-ketoglutarate, and acetyl-CoA, thus being responsible for ATP and macromolecules synthesis, preferentially replacing glucose in certain tumors [ 15 , 16 , 17 ]. Furthermore, glutamine is a precursor of glutamate, which is necessary for the synthesis of non-essential amino acids and glutathione (GSH), the most important reactive oxygen species (ROS) scavenger and detoxifying agent [ 18 , 19 ].…”
Section: Glutamine and Glutamate Metabolism In The Central Nervousmentioning
confidence: 99%
“…We have previously shown the efficacy of PUREG4-FA2 nanoparticles as a vehicle to deliver a cytotoxic selenium-chrysin compound to ovarian cancer cells [28]. In this study, we have shown the efficacy of those nanoparticles as a vehicle to delivery also L-BSO to ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 53%
“…Our previous studies suggested a stronger dependence of ES2 cells on GSH turnover compared with OVCAR3 cells [12,13], which was also evidenced in this study, as higher EC 50 of free l-BSO and l-BSO@PURE G4 -FA 2 were determined for ES2 compared with OVCAR3 cells. Furthermore, concerning resistance to carboplatin, we have reported that upon carboplatin exposure ES2 produce higher levels of GSH [11] together with an accelerated GSH turnover, compared with OVCAR3 [28]. Therefore, our greatest achievements in this study were the effective use of l-BSO@PURE G4 -FA 2 nanoparticles to the specific targeting of malignant cells, decreasing the harmful effects of l-BSO in non-malignant cells, and the similar effective targeting of ovarian cancer cells with different levels of chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among different adaptive strategies adopted by chemoresistant cancer cells, chemoresistance has been associated with alterations in glutathione (GSH) and cysteine dynamics. We and others showed that, overall, cysteine flux in cancer cells and the expression and activity of enzymes involved in cysteine metabolism interfere with the response to chemotherapy by ultimately abrogating the effect of oxidative or alkylating drugs [ 3 , 4 , 5 , 6 , 7 ]. On the other hand, enzymes function is influenced by the oxidative stress.…”
Section: Introductionmentioning
confidence: 99%